Experimental certification of millions of genuinely entangled atoms in a solid - Florian Fröwis; Peter C. Strassmann; Alexey Tiranov; Corentin Gut; Jonathan Lavoie; Nicolas Brunner; Félix Bussières; Mikael Afzelius; Nicolas Gisin (Nature Communications, 2017)
The presence of entanglement in macroscopic systems is notoriously difficult to observe. Here, the authors develop a witness which allow them to demonstrate entanglement between millions of atoms in a solid-state quantum memory prepared by the heralded absorption of a single photon.